Pengembangan Media Math Fun Pembelajaran Operasi Dasar Kelas IV Sekolah Dasar - Marita salsabila; Ida Putri Rarasati; Deny Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the results of a preliminary analysis conducted through observations, interviews, needs assessment questionnaires, and analysis of students' learning outcomes at SDN 01 Nglegok, SDN 02 Nglegok, and SDN 02 Penataran. The analysis revealed that students still experienced difficulties in understanding basic mathematical operations, particularly addition, subtraction, multiplication, and division of whole numbers up to 10,000. Mathematics learning was still dominated by the use of textbooks, student worksheets, and lecture-based instruction, resulting in a lack of interactive learning experiences. Furthermore, students expressed the need for more engaging, interactive, and learner-centered instructional media. Therefore, an interactive PowerPoint-based learning media called math fun was developed, featuring learning materials, instructional videos, interactive quizzes, the mini cashier (si mika) simulation, automatic feedback, and learning evaluations. This study employed a Research and Development (R&D) approach using a modified ADDIE model, covering the Analysis, Design, and Development stages. The sampling technique used was purposive sampling, in which research participants were intentionally selected based on the objectives of the study. The respondents consisted of one material expert, three media expert, three language expert, three fourth-grade teacher as the teacher readability test respondent, and 20 fourth- and fifth-grade elementary school students as the student readability test respondents. Data were collected through observations, interviews, documentation, and questionnaires, and were analyzed using descriptive quantitative analysis by calculating the percentage of product feasibility. The findings indicated that the math fun learning media obtained a media expert validation score of 96.6%, a language expert validation score of 94.6%, and a material expert validation score of 82.6%, all of which were categorized as very feasible. The teacher readability test achieved a score of 80%, categorized as feasible, while the student readability test obtained a score of 94%, categorized as very feasible. These findings indicate that the math fun learning media meets the feasibility criteria for use as a learning medium for basic mathematics operations on whole numbers in fourth-grade elementary schools and has the potential to support a more interactive, engaging, and meaningful learning process.